A systematic investigation on physical properties of spray pyrolysis–fabricated CdS thin films for opto-nonlinear applications: An effect of Na doping. Issue 4 (28th February 2020) - Manthrammel, M. Aslam; Shkir, Mohd.; Shafik, S.; Anis, Mohd.; AlFaify, S.
Abstract: Abstract : The present work investigates the influence of sodium doping on structural, morphological, photoluminescence, linear, nonlinear (NL), and optical limiting (OL) parameters of Na x Cd1− x S thin films (where x = 0.0, 0.5, 1.0, 2.5, and 5.0 wt%) deposited on glass substrates using spray pyrolysis route. X-ray diffraction and Raman analyses confirmed the hexagonal polycrystalline nature of films. Crystallite sizes were decreased from 30 to 17 nm with doping. Scanning electron microscopy (SEM) micrographs also confirmed the nanocrystalline spherical growth. Energy dispersive X-ray spectroscopy (EDS) and SEM mapping studies revealed the presence and homogeneous distribution of individual elements. Transmission of films is found to lie between 45 and 60%. Although the low doping caused the reduction of the effective band gap, higher doping caused a blue shift in band gap, with an associated reduction in crystallite sizes. The refractive index values are found within 1–2 in visible and their maximum values (in range 2.65–3.16) are observed at 2500 nm. Photoluminescence (PL) spectra showed broad emission peak at ∼ 520 ± 10 nm. Dielectric and NL analyses were also carried out. OL results were promising for the systematic gradual decrease of intensity from 100 to 72%, with doping for power regulating applications.